The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1103/physrevd.100.023010
|View full text |Cite
|
Sign up to set email alerts
|

Systematic differences due to high energy hadronic interaction models in air shower simulations in the 100 GeV-100 TeV range

Abstract: The predictions of hadronic interaction models for cosmic-ray induced air showers contain inherent uncertainties due to limitations of available accelerator data and theoretical understanding in the required energy and rapidity regime. Differences between models are typically evaluated in the range appropriate for cosmic-ray air shower arrays (10 15 -10 20 eV). However, accurate modelling of charged cosmic-ray measurements with ground based gamma-ray observatories is becoming more and more important.We assess … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…Secondly the network training is performed using simulated protons as the background events, however significant systematic uncertainties exist in the modelling of hadronic interactions in this energy range [35]. This behavioural uncertainty could result in a reduced performance when applying the trained networks to data due to incorrectly reproducing features within the air shower.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly the network training is performed using simulated protons as the background events, however significant systematic uncertainties exist in the modelling of hadronic interactions in this energy range [35]. This behavioural uncertainty could result in a reduced performance when applying the trained networks to data due to incorrectly reproducing features within the air shower.…”
Section: Discussionmentioning
confidence: 99%
“…The main goal of this research is to understand the hadronic interaction models' deviations in the sub-TeV regime, where they have been seen to significantly disagree [2]. We chose an initial proton energy of 100 GeV (including the rest mass) to perform all simulations.…”
Section: Simulation Methodologymentioning
confidence: 99%
“…In a recent study [2], it was found that for cosmic-ray protons with an energy just above the typical switching energy, the properties of the simulated EASs have a strong dependency on the selection of the hadronic interaction model. With increasing energy of the incident proton (up to 100 TeV), the average differences in air shower properties between the models seemed to reduce.…”
Section: Introductionmentioning
confidence: 99%
“…However a detailed study of these effects is beyond the scope of the work presented here. For a recent systematic study on the impact of the choice of hadronic interaction models on air shower simulation in the energy range of our interest we refer to [23]. The electromagnetic interactions are handled by the EGS4 model [24].…”
Section: Simulations and Atmospheric Propagationmentioning
confidence: 99%